Digital presence and online identity among digital scholars: a thematic analysis - Paiva, Ana Maria Videira (2023)
In today’s postdigital society, the public presence of academics on the Web and the consequent affirmation of a given identity or of a multidimensional identity imply a much more complex and multifaceted management of their image than when we were dealing with a scholar whose identity was affirmed in circumscribed spaces and times. In this work, we seek to analyze the positioning of the subjects about their online identities and the ways in which they express the multiple facets of the construction of their online selves. We adopted a Thematic Analysis approach to qualitative research and used NVivo to analyze the data collected through semi-structured interviews of 13 subjects from a purposive sample of digital scholars. Three major themes were identified: Theme A—Digital-Presence Awareness; Theme B—The Public and the Private Spheres; and Theme C—Offline, Online, and Hybrid Selves. Overall, subjects clearly express the awareness of the need to build a presence on the Web. While there is a general concern to preserve a certain level of authenticity, intimacy, and privacy on the Web, there seems to be some heterogeneity in the experiencing of these processes. For some participants, the distinction between public and private and between personal and professional should be clearly marked, while for others, the necessarily hybrid nature of identity should be assumed, arguing that it is no longer possible to make a clear separation between the offline and the online world. This work, thus, shows different shades in the way academics construct their presence on the Web and how differently they assume several of the constitutive dimensions of their identities.